The impact of university-industry collaboration in SMEs innovation: the CUC-ICONOS case (2022)
This study intends to analyze the impact of university-industry collaboration on SMEs innovations using the data from Universidad de la Costa (CUC) participation on ICONOS Program, in Colombia. Besides describing more traditional outcomes, such as volume and types of innovation, as well as categorize innovations as technology push and market pull, this paper explores the potential mutualism of the interaction based on the model of Shaeffer et al. (2021). Document analysis and additional interviews allowed the integration of 104 sources on the final proposed framework of interactions. Results infer the existence of a very significant mutualistic relationship as well as the presence of a cyclical flow, in which results become new inputs for each agent.